Divulgación de información sobre responsabilidad social: Comparación entre la empresa pública versus privada en España (2015)
The aim of this paper is the comparative analysis of the online information disclosed regarding social responsibility between public and private companies, as well as their determining factors. To this end, a comparative analysis followed by a multiple regression analysis was performed. The findings indicate that public companies have greater availability of information in their websites concerning the economic and environmental impact of their activities than private ones. Likewise, it is evidenced that “type of property” is a determining factor for transparency practices.